Chemical composition and biological activities of essential oils of endemic Thymus leucostomus Hausskn. et Velen (Bangladesh Journal of Botany, 2020)
The chemical composition, antimicrobial and antioxidant properties of the essential oils from the leaves of endemic Thymus leucostomus naturally grown in Turkey were investigated and chemical differences were discussed by means of chemotaxonomy. Twenty-six components were identified representing 98.8% of the oils. The main compounds in the essential oil of T. leucostomus were: o-cymene (30.6%), carvacrol (9.6%), thymol methyl ether (7.2%), limonene (6.8%). Essential oil was screened for their antimicrobial activities against 7 bacteria and 2 yeast species by using disc-diffusion and MIC procedure. The essential oil showed higher effectiveness against all the tested bacteria and yeast. The extract was observed to be much more effective in Gram-positive bacteria (especially, S. aureus ATCC 6538). In vitro antioxidant activity based on the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical was evaluated for the essential oil, and it was found that the essential oil had good antioxidant activity in the range of the IC50= 5.42 ±0.8 μg/ml.